Konseling Analisis Transaksional: Sebuah Tinjauan Literatur - Bakhrudin All Habsy; Disma Nadya Shakila; Dhiya Khofifah; Rendy Nuril Anwar (Lembag, 2024)
Transactional analysis counseling was developed from Sigmund Freud's psychoanalytic theory and the discovery of the workings of the brain. The aim of this research is to find out about transactional analysis counseling philosophically based on the results of literature studies. This research uses qualitative methods with a literature study type. The method used in this type of literature study is to search for data or material by reviewing and collecting information from various credible and relevant sources such as scientific journals, articles, books and others related to the topic discussed, namely transactional analysis counseling based on ego state counseling theory. Then note down the important points that are appropriate to the research problem. (1) The results of this research include the Basic Philosophy of Transactional Analysis Counseling. (2) Main Concepts of Transactional Analysis Counseling (3) Objectives of Transactional Analysis Counseling, (4) Ego state theory, (5) Role and function of the counselor in transactional analysis counseling, (6)Counselee experience in counseling. (7) Procedure for Transactional Analysis Counseling Stages. (8) Transactional Analysis Counseling Techniques.